2019
DOI: 10.34019/1982-8047.2019.v45.16970
|View full text |Cite
|
Sign up to set email alerts
|

Low health literacy in older patients with uncontrolled blood pressure at secondary care

Abstract: Background: Low health literacy (LHL) is common among patients with chronic diseases. Studies on the association between LHL and uncontrolled blood pressure are limited to primary and tertiary levels of healthcare. Objective: We evaluated the prevalence and association between LHL and uncontrolled blood pressure in hypertensive patients in a secondary healthcare in Brazil. Material and methods: Our study had a cross-sectional design and included 485 patients, between August/2014 to March/2016. We evaluated hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Four studies ( n = 729; 3.0%) [ 41 , 46 , 68 , 85 ] evaluated a population under 30 years of age, and 35 studies ( n = 8,315; 34.8%) [ 12 , 14 , 16 , 25 , 26 , 29 , 31 , 32 , 35 , 40 , 44 , 45 , 48 , 50 , 51 , 53 , 54 , 56 , 57 , 60 , 62 – 64 , 66 , 67 , 69 , 71 , 79 , 82 , 86 , 89 , 90 , 92 , 93 , 95 ] assessed HL in adults with an average age between 30 and 60 years of age. 25 studies had a population with an average age above 60 years ( n = 5,870; 24.5%) [ 13 , 15 , 17 , 21 , 24 , 28 , 33 , 37 39 , 42 , 49 , 55 , 59 , 61 , 65 , 70 , 75 77 , 81 , 83 , 84 , 88 , 91 ]. In the mean years of formal education, 1,849 (7.7%) [ 13 , 16 , 26 , 29 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies ( n = 729; 3.0%) [ 41 , 46 , 68 , 85 ] evaluated a population under 30 years of age, and 35 studies ( n = 8,315; 34.8%) [ 12 , 14 , 16 , 25 , 26 , 29 , 31 , 32 , 35 , 40 , 44 , 45 , 48 , 50 , 51 , 53 , 54 , 56 , 57 , 60 , 62 – 64 , 66 , 67 , 69 , 71 , 79 , 82 , 86 , 89 , 90 , 92 , 93 , 95 ] assessed HL in adults with an average age between 30 and 60 years of age. 25 studies had a population with an average age above 60 years ( n = 5,870; 24.5%) [ 13 , 15 , 17 , 21 , 24 , 28 , 33 , 37 39 , 42 , 49 , 55 , 59 , 61 , 65 , 70 , 75 77 , 81 , 83 , 84 , 88 , 91 ]. In the mean years of formal education, 1,849 (7.7%) [ 13 , 16 , 26 , 29 ,…”
Section: Resultsmentioning
confidence: 99%
“…25 studies had a population with an average age above 60 years ( n = 5,870; 24.5%) [ 13 , 15 , 17 , 21 , 24 , 28 , 33 , 37 39 , 42 , 49 , 55 , 59 , 61 , 65 , 70 , 75 77 , 81 , 83 , 84 , 88 , 91 ]. In the mean years of formal education, 1,849 (7.7%) [ 13 , 16 , 26 , 29 , 40 , 54 , 69 , 85 ] participants had eight years or more of schooling, and 1,247 (5.2%) [ 15 , 55 , 65 , 81 ] had less than eight years of schooling. The table with the individual characteristics of the included studies is in Additional file 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of social determinants, it is observed that individuals belonging to ethnic groups who are victims of social adversity and with low schooling are more likely to have low levels of FHL and, consequently, are predisposed to worse health status 21 . In this sense, a study conducted with North American adults observed that non-white individuals were more likely to have low or limited FHL 22 .…”
Section: Discussionmentioning
confidence: 99%